A Critical Analysis of Breast Milk Enrichment in Distinct Bioactive Molecules: A Study of the Developmental Roles and Immunological Responses in the Newborn - Dr. Etini Aniekan Otumo (Genius Journals, 2023)
The study aimed to analyze breast milk enrichment in distinct bioactive molecules as a study of the developmental roles and immunological responses in the new born. Breast milk is milk produced by mammary glands located in the breast of a human female. Breast milk is the primary source of nutrition for newborns, containing fat, protein, carbohydrates and variable minerals and vitamins. Human breast milk is a complex mixture of organic and inorganic compounds. Some compounds, such as conjugated linoleic acid (CLA), come partly from the mother's diet and are produced by the mother's body and secreted into the milk. The benefit of breast milk cannot be overemphasized; breast milk provides protection for the health of the infant during the first weeks of life, breastfeeding also improves the neuro development of children born immature. The paper reviewed the concept of breast milk, the concept of breast milk enrichment, the concept of bioactive molecules, and the roles of breast milk in the development of new born. It was this basis that the study concluded that Human milk is the best food for newborn nutrition. There is no ideal composition of human milk and also no easy way to control the complexity of its nutritional quality and the quantity received by breastfed infants. The benefits of breastfeeding have been quantified economically and increased breastfeeding rates bring substantial savings for any health system. One of the recommendations made was that women should appreciate the fact that breast milk provides distinct bioactive molecules that contribute to immune maturation, organ development, and healthy microbial gut colonization. Hence, they should encourage their babies with it regularly in order to protect newborn against infection, stomach bugs and inflammation.
Keywords: Breast Milk Enrichment; Distinct Bioactive Molecules; Developmental Roles